Poor Settlements in Chittagong city, Bangladesh: The context of Pollution and Health Risk (Quest Journal of Management and Social Sciences, 2019)
Background: The rapid rate of urbanization in Bangladesh has created some adverse effects on the overall urban environmental health of the cities. Among all, mass poverty, expansion of poor neighbourhood, inadequate supply of urban services such as water, sanitation, waste disposal etc. are mostly responsible for health risks of urban people particularly in low income areas.Objectives: The aim of this paper is to determine the health risks of the environmentally poor neighbourhoods in Chittagong city by exploring the discourse of pollution, risk, and stigma.Methods: The study is predominantly based on qualitative data collection methods like participant observations, a case study and FGDs. The method has delivered an in-depth understanding of the pollution-related risks, the physical and mental sufferings of the urban poor due to  pollution. Though it is solely a qualitative study, the study is complemented  by a quantitative survey method and  personal interviews.Findings: The study revealed that there are two leading environmental risk factors– the structural setting of the neighbourhood and coping practices to everyday life of the poor settlers, who  affect the neighbourhood environment. The poor structured living houses, shared kitchens in the environmentally hazardous area, dirty playgrounds, unhygienic latrines, and waste disposal sites near neighbourhoods enhance the risk of diseases and injuries for inhabitants. Similarly, lack of access to pure drinking water, fuel, are generating health risks. Consequently, dwellers, especially women and children, suffer from cough and cold, diarrhoea, gastric/acidity, worm disease, respiratory illness, scabies, headache, allergy, and jaundice regular interval of time.Conclusion: The study concludes that  physical structure of the neighbourhood, and the physical and mental sufferings of its inhabitants are interdependent. To reduce the sufferings of inhabitants and their health hazards can be reduced with the combined efforts of the  Government and the NGOs and  the local people as well. Implications: This findings of the study can be useful to the  concerned authorities of Bangladesh in planning appropriate policies to  control pollution and minimize health risks.  For that purpose this study can serve as reference.